EKSISTENSI HUKUM ADAT DAN IMPLIKASINYA TERHADAP PENYELESAIAN SENGKETA LAHAN DALAM PROYEK PEMBANGUNAN INFRASTRUKTUR - CAHYA CITRA AULIA; Balqis Febriant Ratu Fadhillah; Putra Tindaon; Muhammad Rafi Fernanda Harahap (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study examines the persistence of adat law as a social norm system still prevalent in various local communities, and its impact on land dispute resolution mechanisms in the context of infrastructure development projects. Focusing on the interplay between traditional rules and state regulations, this research aims to identify how the existence of adat law influences the effectiveness of land conflict resolution, which often arises from tensions between development interests and indigenous rights. The research employs a qualitative approach through legal document analysis, in-depth interviews with stakeholders, and case studies in several Indonesian regions experiencing major infrastructure projects. The findings reveal that adat law, although often considered subordinate to positive law, plays a crucial role in fostering trust and social justice, thereby accelerating dispute resolution through customary deliberation mechanisms. However, its implications also include challenges such as inconsistent interpretations and potential conflicts with national policies, necessitating better integration between the two legal systems. The study's conclusion advocates for the development of a hybrid resolution model that respects adat values while ensuring compliance with sustainable development goals, to reduce project stagnation risks and enhance community welfare. This research contributes to adat law literature by providing practical insights for infrastructure development policies in developing countries.